Answer: $9 dollars
Step-by-step explanation:
27 divided by 3 = 9
*** If you found my answer helpful please give me the brainliest :) ***
4(0.5n-3)=n-0.25(12-8n)
2n-12=n-3+2n
2n-12=3n-3
2n-3n=-3+12
-n=9
n = -9
We do like the following:
Set the first number is a and the second is b.
We have two equations: a+2xb=24, 2xa+b=21
And we have 2xa+4xb=48 or 2xa=48-4xb
So: 48-4xb+b=21 or -3xb=21-48=-27 and we got b=-27:(-3)=9 and a= 6
a=6 and b=9
To solve an equation with a rational (fraction) coefficient you need to multiply both sides of the equation by the reciprocal (invert the fraction - flip it).
![\frac{1}{6}x =4](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B6%7Dx%20%3D4)
The reciprocal of 1/6 is 6/1 or 6
![6( \frac{1}{6} x)= 6(4)](https://tex.z-dn.net/?f=6%28%20%5Cfrac%7B1%7D%7B6%7D%20x%29%3D%206%284%29)
The product of reciprocals equals 1
1x = 24
x = 24
Answer:
D
Step-by-step explanation: